Persistent COVID and ASD: Long-term neuropsychiatric impact and the need for personalized interventions - Gallardo Herrerias, Celia (Revista de Estudios Socioeducativos. ReSed, 2025)
The study explores the long-term neuropsychiatric impact of COVID-19 on individuals with Autism Spectrum Disorders (ASD) in order to develop effective interventions and treatments. The primary objective was to examine the impact of COVID-19 on long-term neuropsychiatric symptoms in ASD patients and determine the optimal treatment and management options. A systematic review was performed using scientific databases such as PubMed, Scopus, Web of Science, and Redalyc, with major key words and strict inclusion/exclusion criteria to ensure the quality of the study. Of the 242 studies initially reported, 12 met all the inclusion criteria for the review. The outcomes showed that repeat COVID aggravates pre-existing neuropsychiatric signs in ASD individuals, mainly depression and anxiety. Meta-analysis of the combined studies showed an increase of 1.5 points on a common symptom score after COVID-19. Irritability and emotion regulation were also identified as other behavioral problems. Overall, COVID-19 impacts the neuropsychiatric health of ASD individuals adversely and demands tailored and multidisciplinary treatment methods targeting physical as well as psychiatric symptoms.